Prenatal and neonatal factors for the development of childhood visual impairment in primary and middle school students: a cross-sectional survey in Guangzhou, China. Issue 9 (9th September 2020) - Yu, Bolan; Dai, Lijuan; Chen, Juanjuan; Sun, Wen; Chen, Jingsi; Du, Lili; Deng, Nali; Chen, Dunjin
Abstract : Objectives: In this cross-sectional survey, we sought to determine the prevalence of and the influence of prenatal and neonatal factors on childhood visual impairment without correction (VIUC) in a paediatric population from Guangzhou, China. Setting: The health survey covered 11 administrative districts in Guangzhou, including 991 schools. Participants: All of the primary and middle school students in Guangzhou were invited to complete an online questionnaire with the help of their parents. The results of physical examinations were reported by school medical departments. The results of the questionnaire were collected by the researchers. In total, 253 301 questionnaires were collected. Primary outcome measures: The students' uncorrected visual acuity (UCVA) was examined by trained optometrists by standard logarithmic visual acuity charts. VIUC was defined by UCVA (of the better eye) (UCVA <6/12) with three levels: light VIUC (UCVA ≥6/18 to <6/12), mild VIUC (UCVA ≥6/60 to <6/18) and severe VIUC (UCVA <6/60). Results: A total of 39 768 individuals (15.7%) had VIUC, and the rate was much higher among grade 10 to 12 students (51.4%) than among grade 1 to 6 students (6.71%). The following factors were significantly associated with an increased risk of VIUC: female gender, high birth weight, formula feeding, not having siblings, higher level of parents' education, parental myopia, much homework time and little outdoor activity. Delivery mode was not associated with the risk of VIUC. Conclusions: This study validates known major prenatal/genetic, perinatal and postnatal factors for childhood VIUC. In conclusion, prenatal and perinatal factors can affect the onset of childhood VIUC, but parental myopia and postnatal factors are the main factors.